2021
DOI: 10.3390/healthcare9050574
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Protective Behaviors and Risk Perception of COVID-19 among Dental Students in India: A Cross-Sectional Analysis

Abstract: Objective: This study’s objective was to examine the knowledge, performance in practicing protective behaviors, and risk perception of Coronavirus disease-19 (COVID-19) among dental students of India. Methods: A web-based cross-sectional survey was conducted from 10–30 August 2020, involving 381 dental students that were enrolled at the Uttaranchal Dental and Medical Research Institute in India. A web-based structured questionnaire assessed the COVID-19 related knowledge, protective behaviors, and risk percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 40 publications
(82 reference statements)
4
36
1
Order By: Relevance
“…Interestingly, one of the identified factors ("Modality of teaching") suggests that students that were less likely to report to miss social contact with their teachers and peers, suggesting less need for social interaction, also appreciated various aspects of online learning more. With the rise of distance learning, a growing number of studies are looking to identify students' personality traits and behaviours influencing their preferences for different modalities of education [33][34][35][36][37]. The data could be considered instrumental in structuring effective teaching and learning systems, accommodating different student learning styles.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one of the identified factors ("Modality of teaching") suggests that students that were less likely to report to miss social contact with their teachers and peers, suggesting less need for social interaction, also appreciated various aspects of online learning more. With the rise of distance learning, a growing number of studies are looking to identify students' personality traits and behaviours influencing their preferences for different modalities of education [33][34][35][36][37]. The data could be considered instrumental in structuring effective teaching and learning systems, accommodating different student learning styles.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [37] reported that dental specialists showed adequate knowledge regarding preventive measures. Furthermore, a recent study [38] suggested that it is imperative to promote the infection control protocols among dental students through training programs to avoid the potential risk of COVID-19. Cori et al [39] opined that government authorities' administration of risk communication is required to establish consciousness and rationality.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that open communication among students, clinical teachers, and administrative staff would enhance mutual trust and facilitate adequate cooperation at a time of particular epidemic danger [ 30 ]. Batra et al proved that dental students had sufficient knowledge regarding the COVID 19 pandemic but also showed that there is a need to restructure the educational curriculum to prepare students to handle COVID-19 and future pandemics [ 31 ]. Studies show pandemics, such as COVID-19 increased psychological stress, and the consequences of quarantine might lead to emotional disturbance, depression, irritability, insomnia, anger, and emotional exhaustion among other health and mental health conditions [ 4 , 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys conducted among Chinese students indicated that the public perception of health risks among college students in China presented valuable information on their perception of health risks. Generally, the hazards that were perceived as posing the greatest health risk were those belonging to the social health risk category; items related to technology risks received the lowest percentage [ 31 ]. University students played a particularly important role in debates about voluntary quarantines for SARS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation